Analysis of trend in area, production and productivity of okra (Abelmoschus esculentus) in India (Current Horticulture, 2024)
The analysis of production and area under okra (Abelmoschus esculentus Linn.) in India showed a perceptible trend in growing preference of okra crops among farmers. There is a decline in growth rate of yield of okra. The analysis also showed that though there is a steady increase in the area as well in production under okra crops. The growth rate as well as forecasting from 2017-18 to 2020-21 showed the increasing trend. Graphical representation also showed the increasing trend of okra.
Keywords: Trend; Linear model; Growth rate; Forecasting; Productivity